The effect of Lignova sorbent to the concentration of interleukin-6 in the blood and bile in patients with mechanical jaundice of tumors etiology - N. U. Aripova; U. S. Ismailov; S. R. Baymakov; A. A. Adilkhodjaev; M. M. Pulatov; S. K. Matmuratov; S. I. Jamalov; S. Sh. Yunusov (Вестник хирургии имени И.И. Грекова)
The OBJECTIVE was to study changes of IL-6 concentration in the blood and bile in patients with MJ of tumor genesis by means of biliary sorption.METHODS AND MATERIALS. The investigation was conducted to study changes in the concentration of IL-6 in the blood and bile against the background of bile sorption in 105 patients with mechanical jaundice (MJ), the cause of obturation was a tumor of the periampullary zone. The patients are divided into two groups. The first group consisted of 51 patients, the second group included 54 patients. All patients of the main group underwent percutaneous perhepatic cholangiostomy for the purpose of decompression; bile sorption was performed using the domestic Lignov enterosorbent. The level of IL-6 in blood serum and bile was determined by enzyme immunoassay.RESULTS. The use of bile sorption in the treatment complex significantly changed the concentration of IL-6 in blood serum (P<0.01) and bile. Determination of IL-6 in blood and bile makes it possible to more objectively assess the degree of cytokine-induced endogenous intoxication in response to ongoing therapeutic measures for tumors of the periampullary zone complicated by mechanical jaundice. The use of bile sorption contributes to a decrease in the concentration of the pro-inflammatory cytokine IL-6 in the blood and bile as an inducer of endogenous intoxication and a cascade of inflammatory processes in patients with tumors of the periampullary zone complicated by mechanical jaundice.CONCLUSION. Bile sorption application helps to decrease proinflammatory cytokine IL-6 concentration in blood and bile as an inductor of endogenous intoxication and inflammatory processes cascade.